2017
DOI: 10.1007/s13205-017-0900-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficient biodegradation of acephate by Pseudomonas pseudoalcaligenes PS-5 in the presence and absence of heavy metal ions [Cu(II) and Fe(III)], and humic acid

Abstract: The present study was intended to investigate the biodegradation of acephate in aqueous media in the presence and in the absence of metal ions [Fe(III) and Cu(II)], and humic acid (HA). Biodegradations were performed using PS-5 (PS-5) isolated from the heavy metal polluted site. Biodegradations were monitored by UV-Visible, FTIR, and electron spray ionization-mass spectrometry (ESI-MS) analyses. ESI-MS analysis revealed that PS-5 degraded acephate to two metabolites showing intense ions at mass-to-charge ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…These studies are applicable to all the molecules containing secondary amine [60][61][62][63]. After the derivatization, UV-visible analysis can be used to detect these molecules from various compartments of the environment [54][55][56][57][58][59][60][61][62][63]. In our recent study, we have found that acephate and glyphosate were detectable by UV-visible, FTIR, mass and NMR studies [60,63].…”
Section: Environmental Applicabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…These studies are applicable to all the molecules containing secondary amine [60][61][62][63]. After the derivatization, UV-visible analysis can be used to detect these molecules from various compartments of the environment [54][55][56][57][58][59][60][61][62][63]. In our recent study, we have found that acephate and glyphosate were detectable by UV-visible, FTIR, mass and NMR studies [60,63].…”
Section: Environmental Applicabilitymentioning
confidence: 98%
“…These studies are very important, especially with environmental concern and real-world analysis applications. For example, the detection of glyphosate by UV-visible spectrophotometric methods which are reliable and belongs to real-time analysis, interactions of pesticides with the soils and their adsorption on clay and humates [41][42][43][44][45][46][47][48][49][50][54][55][56][57][58][59][60][61][62][63]. These studies are the foundation of detection of various contaminants and their metabolites through the chromatographic methods in water, soils, fruits, crops, vegetables and other samples [41][42][43][44][45][46][50][51][52][53][54][55][56]64].…”
Section: Environmental Applicabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the data obtained by Abu El-Soud et al (2013) who indicated that the application of ellagic acid to chickpea plants mitigated effects of stress by reducing ROS content. Moreover, some of the recent studies showed that the application of phenolic acids such as gallic and cinnamic acid alleviated the oxidative damage induced by stress via lessening H 2 O 2 and TBARS contents and increasing antioxidant capacity (Ozfidan-Konakci et al, 2015;Singh et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…These are costly, time-consuming, and inefficient techniques and can lead to the formation of toxic metabolites, i.e., side-products of pesticides. On the other side, the use of microorganisms is an effective way to decompose pesticides in a green or eco-friendly manner [7]. These microbe-based techniques are efficient in eradicating hazardous compounds from different ecosystems.…”
Section: Introductionmentioning
confidence: 99%